1997
DOI: 10.1111/j.1095-8649.1997.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

The critical swimming velocity of diploid and triploid brook trout

Abstract: No significant difference was found in the critical swimming velocity of diploid and triploid brook trout Salvelinus fontinalis, suggesting that the triploid state is not associated with a reduced aerobic capacity. 1997 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Other experiments about the critical swimming speed used as indicator of aerobic capacities have evidenced a similar lack of triploidy‐induced effect (Small and Randall 1989; Sezaki et al. 1991; Parsons 1993; Stillwell and Benfey 1996, 1997; Altamiras et al. 2002).…”
Section: Environmental Tolerancementioning
confidence: 57%
“…Other experiments about the critical swimming speed used as indicator of aerobic capacities have evidenced a similar lack of triploidy‐induced effect (Small and Randall 1989; Sezaki et al. 1991; Parsons 1993; Stillwell and Benfey 1996, 1997; Altamiras et al. 2002).…”
Section: Environmental Tolerancementioning
confidence: 57%
“…Measurements of aerobic capacity revealed no deficiency in triploid salmonids (Ojolick et al, 1995;Stillwell and Benfey, 1997), and tests on exhaustive exercise in brook trout, Salvelinus fontinalis, triploids showed that aerobic and anaerobic capacities of triploids were only compromised relative to diploids at high temperatures (Hyndman et al, 2003a(Hyndman et al, , 2003b. Further, forced swimming in triploid Atlantic salmon demonstrated no difference in their aerobic capacity compared with diploids, but anaerobic capabilities were affected (Cotterell and Wardle, 2004).…”
Section: Fishmentioning
confidence: 98%
“…Sub-optimal rearing conditions can lead to poorer performances of triploids. Examples include defective adjustment to seawater culture in salmonids (Johnson et al, 1986;Quillet et al, 1987;Quillet and Gaignon, 1990;Galbreath and Thorgaard, 1995;Ojolick et al, 1995;Chevassus, 1998;Bonnet et al, 1999), high rearing temperatures in rainbow trout (Ojolick et al, 1995), grow out at high stocking density and communal culture in grass carp (Cassani and Caton, 1986) and low level of dissolved oxygen in salmonids (Quillet at al, 1987;Quillet and Gaignon, 1990;Johnstone et al, 1991;Ojolick et al, 1995;Stillwell and Benfey, 1997;Bernier et al, 2004) and European sea bass (J.-C.…”
Section: Fishmentioning
confidence: 99%